THE RELATIONSHIP OF FLOOD DISASTER WITH THE INCIDENCE OF DIARRHEA, WATER QUALITY AND COMMUNITY RESILIENCE IN WATER SUPPLY: A CASE STUDY IN THE CITY OF BUKITTINGGI - Putri Nilam Sari; Nofriya Nofriya (Faculty of Public Health, Andalas University, 2018)
Bukittinggi is a city in West Sumatra that become potential area for flooding. It is followed by increasing of diarrhea diseases. This also affects water quality. Bukittinggi is having problems with the provision of adequate clean water in accordance with the target of Sustainable Development Goals. This study aims to determine the relationship of floods to the incidence of diarrhea, water quality and community resilience in providing clean water for everyday life. The method used through a quantitative approach with cross-sectional design and conducted in December 2017 until January 2018. The results show the relationship between floods with diarrhea occurrence, water difficulty, water quality (smelly water, dirty water and the presence of insects and worms), as well as community resilience to help each other in water supply and water source storage to avoid contamination. It is advisable for the government to increase its social capacity in the provision of clean water because the city of Bukittinggi is vulnerable to floods that would damage water sources.